Membaca Al Fatihah Reflektif Intuitif untuk Menurunkan Depresi dan Meningkatkan Imunitas - Julianto, Very; Subandi, Subandi (Jurnal Psikologi, 2015)
This study aimed to reduce depression and increase immunity through training of reading of the reflective intuitive Al-Fatihah. Researchers used an experimental method with pretest-posttest control group design. Each experimental group and control group consisted of 10 students of Islamic Boarding School. To measure stress degree, Depression Anxiety Stress Scale (DASS) was used. Immunity was measured with microscopic slide method using hematology analyzer. Quantitative analysis was done through a mixed design anova statistical test. The results showed that the training could reduce depression (F=15.34, p